Ethics in Social Science: A Long Way to Go - Orlans, Harold (The Hastings Center report, 1979)
Book reviewed in this article: Ethics in Social and Behavioral Research. By Edward Diener and Rick Crandall The Ethics of Social Intervention. Gordon Bermant, Herbert C. Kelman, Donald P. Warwick